KAJIAN ASPEK HUKUM TERHADAP PEMBERLAKUAN JAMINAN PENAWARAN PADA PELELANGAN JASA PELAKSANAAN KONSTRUKSI (Studi Pada Pelelangan Satker Pelaksanaan Jalan Nasional Wilayah I Provinsi Kalimantan Barat)â€ - HERMAN, S.T. NPM.A2021151065, JURNAL MAHASISWA S2 HUKUM UNTAN (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACTThis thesis discusses Legal Aspect Review on the Enforcement of Bid Security at Auction of Construction Implementation Service (Study On The Auction of Implementation Working Unit of Region I National Road of West Kalimantan Province). The approach method used in this research is sociological normatife approach. Enforcement of Bid Security Requirements at Auction of Construction Implementation Services In Perpres No. 4 of 2015 In Delete. The implementation of E-Tendering shall be carried out under the following conditions: No Bid Security shall be required, no qualification shall be required, if the bid is less than 3 (three) participants, the selection of the provider shall be followed by technical negotiation and price / cost, no counter appeal is required Selection of Consultant, shortlist of 3 (three) to 5 (five) Consultants, Simple Selection is done by post-qualification method. Presidential Institution In Making Presidential Regulation Number 4 Year 2015 Concerning Fourth Amendment Of Presidential Regulation Number 54 Year 2010 About Procurement of Government Goods / Services Contrary With Norms Of Law Which Is Above That Is A Construction Service Law Number 18 Year 1999 Which To Cover And Become One Of The Source Of Law . The Presidential Regulation in the enactment of Presidential Regulation No. 4 of 2015 concerning the fourth amendment of Presidential Decree Number 54 Year 2010 concerning Procurement of Government Goods / Services shall begin to imply the necessity of procurement managers, both committing officers and procurement committee and procurement officials, to be eligible from eligible personnel , Both integrity, managerial and competence. The requirements specified in the Presidential Regulation in the enactment of Presidential Regulation No. 4 of 2015 concerning the fourth amendment of Presidential Regulation Number 54 Year 2010 concerning Procurement of Government Goods / Services illustrates that the parties involved in it have different focus on the requirements of competence. Competence ranging from aspects of leadership, technical and managerial. The Presidential Regulation shall be a Legislation stipulated by the President to enforce higher orders of the Law and in the exercise of governmental power. Policy of the Ministry of Public Works and Public Housing In Carrying Out Auction of Construction Service Implementation Related to Presidential Decree Number 4 of 2015. Presidential Regulation No. 4 of 2015 on Fourth Amendment Perpres No. 54 of 2010 on Article 23 paragraph (2) which is: K / L / D / I provide support costs for the implementation of Procurement of Goods / Services financed from the APBN / APBD, which includes the honorarium of the Procurement organization personnel including the technical team, the support team and project staff, the cost of announcing Procurement of Goods / Services including the cost of re-announcement, the cost of duplicating the Document Procurement of Goods / Services and other necessary costs. Recommendation: The government needs to socialize Presidential Decree number 80 year 2003 and then regulated in more detail at Perpres number 54 year 2010. And berdasrkan President in making Presidential Regulation No. 4 of 2015 about the fourth change of Presidential Regulation No. 54 of 2010 on Procurement of goods / services contrary to the Government With legal norms that are above it is the Construction Services Act No. 18 of 1999 which shade and become one of the source of Law. Socializing the Implementation of Bid Security Requirements At Auction Construction Service Implementation In Presidential Regulation Number 4 Year 2015 has been deleted.Â ABSTRAKTesis ini membahas Kajian Aspek Hukum Terhadap Pemberlakuan Jaminan Penawaran Pada Pelelangan Jasa Pelaksanaan Konstruksi (Studi Pada Pelelangan Satker Pelaksanaan Jalan Nasional Wilayah I Provinsi Kalimantan Barat). Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan normatife sosiologis. Pemberlakuan Persyaratan Jaminan Penawaran Pada Pelelangan Jasa Pelaksanaan Kontruksi Di Dalam Perpres Nomor 4 Tahun 2015 Di Hapus. Pelaksanaan E-Tendering dilakukan dengan ketentuan sebagai berikut : tidak diperlukan Jaminan Penawaran, tidak diperlukan sanggahan kualifikasi, apabila penawaran yang masuk kurang dari 3 (tiga) peserta, pemilihan penyedia dilanjutkan dengan dilakukan negosiasi teknis dan harga/biaya, tidak diperlukan sanggahan banding, untuk pemilihan Penyedia Jasa Konsultansi, daftar pendek berjumlah 3 (tiga) sampai 5 (lima) penyedia Jasa Konsultansi, Seleksi sederhana dilakukan dengan metode pasca kualfikasi. Lembaga Kepresidenan Dalam Membuat Peraturan Presiden Nomor 4 Tahun 2015 Tentang Perubahan Keempat Dari Perpres Nomor 54 Tahun 2010 Tentang Pengadaan Barang/Jasa Pemerintah Bertentangan Dengan Norma Hukum Yang Berada Diatasnya Yaitu Undang-Undang Jasa Konstruksi Nomor 18 Tahun 1999 Yang Menaungi Serta Menjadi Salah Satu Sumber Hukum. Peraturan Presiden dalam membuat Peraturan Presiden Nomor 4 Tahun 2015 tentang perubahan keempat dari Perpres Nomor 54 Tahun 2010 tentang Pengadaan Barang/Jasa Pemerintah sendiri mulai mengisyaratkan perlunya pengelola pengadaan, baik pejabat pembuat komitmen maupun panitia pengadaan dan pejabat pengadaan, harus dipilih dari personil yang memenuhi syarat, baik integritas, manajerial maupun kompetensi. Persyaratan-persyaratan yang disebutkan dalam Peraturan Presiden dalam membuat Peraturan Presiden Nomor 4 Tahun 2015 tentang perubahan keempat dari Perpres Nomor 54 Tahun 2010 tentang Pengadaan Barang/Jasa Pemerintah memberi gambaran bahwa para pihak yang terlibat didalamnya memiliki perbedaan fokus persyaratan kompetensi. Kompetensi tersebut mulai dari aspek kepemimpinan, teknis maupun manajerial. Peraturan Presiden adalah Peraturan Perundang-undangan yang ditetapkan oleh Presiden untuk menjalankan perintah Peraturan Perundang-undangan yang lebih tinggi atau dalam menyelenggarakan kekuasaan pemerintahan. Kebijakan Kementerian Pekerjaan Umum Dan Perumahan Rakyat Dalam Melaksanakan Pelelangan Jasa Pelaksanaan Konstruksi Kaitannya Dengan Perpres Nomor 4 Tahun 2015. Peraturan Presiden Nomor 4 Tahun 2015 tentang Perubahan Keempat Perpres Nomor 54 Tahun 2010 pada Pasal 23 ayat (2) yang isinya : K/L/D/I menyediakan biaya pendukung pelaksanaan Pengadaan Barang/Jasa yang dibiayai dari APBN/APBD, yang meliputi honorarium personil organisasi Pengadaan Barang/Jasa termasuk tim teknis, tim pendukung dan staf proyek, biaya pengumumanÂ PengadaanÂ Barang/JasaÂ termasuk biaya pengumuman ulang, biaya penggandaanÂ Dokumen Pengadaan Barang/Jasa dan biaya lainnya yang diperlukan. Rekomendasi : Pemerintah perlu mensosialisasikan Keppres nomor 80 tahun 2003 dan kemudian diatur lebih detail lagi pada Perpres nomor 54 tahun 2010. Dan berdasrkan Presiden dalam membuat Peraturan Presiden Nomor 4 Tahun 2015 tentang perubahan keempat dari Perpres Nomor 54 Tahun 2010 tentang Pengadaan Barang/Jasa Pemerintah bertentangan dengan Norma Hukum yang berada diatasnya yaitu Undang-Undang Jasa Konstruksi Nomor 18 Tahun 1999 yang menaungi serta menjadi salah satu sumber Hukum. Mensosialisasikan Pemberlakuan Persyaratan Jaminan Penawaran Pada Pelelangan Jasa Pelaksanaan Kontruksi Di Dalam Perpres Nomor 4 Tahun 2015 telah di hapus.Â Kata Kunci : Aspek Hukum,Jamaninan Penawaran, Pelelangan,Jasa Kontruksi.